Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1089/107999099313695
|View full text |Cite
|
Sign up to set email alerts
|

The Interleukin-10 Signal Transduction Pathway and Regulation of Gene Expression in Mononuclear Phagocytes

Abstract: Interleukin-10 (IL-10) activates a diverse array of functional responses in mononuclear phagocytes. Functional IL-10 receptor (IL-10R) complexes are tetramers consisting of two IL-10R1 polypeptide chains and two IL-10R2 chains. Binding of IL-10 to the extracellular domain of IL-10R1 activates phosphorylation of the receptor-associated Janus tyrosine kinases, JAK1 and Tyk2. These kinases then phosphorylate specific tyrosine residues (Y446 and Y496) on the intracellular domain of the IL-10R1 chain. Once phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
292
0
6

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(328 citation statements)
references
References 81 publications
22
292
0
6
Order By: Relevance
“…4, C and D). The dampening of TNF-␣ production is mediated through numerous, mechanically distinct, mechanisms involving diverse, intracellular signaling pathways (55)(56)(57). The particular mechanism in our model remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…4, C and D). The dampening of TNF-␣ production is mediated through numerous, mechanically distinct, mechanisms involving diverse, intracellular signaling pathways (55)(56)(57). The particular mechanism in our model remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 binds to a receptor tetramer complex that activates phosphorylation of Janus tyrosine kinases, JAK1 and Tyk2, which then phosphorylate two specific tyrosine residues that form part of a docking site for signal transducer and activator of transcription-3 (STAT-3). STAT-3 is tyrosine phosphorylated by the receptor associated JAKs and then translocates to the nucleus where it binds to STAT binding elements in the promoters of various genes (49). Ricchetti and colleagues found that IL-10-induced expression of HO-1 requires STAT-3 in macrophage cell lines.…”
Section: Mp Ho-1 In Tissue Homeostasismentioning
confidence: 99%
“…Because SOSC3 can negatively regulate responses to different activating cytokines and bacterial products, it is speculated that the anti-inflammatory action of IL-10 is due to induction of SOCS3 [42] . Here, however, our analysis of the expression of IL-10/STAT3 signaling shows that the irradiation-induced SOCS3 overexpression was instead associated with suppression of IL-10 mRNA and STAT3 protein.…”
Section: Irradiation Induced Expression Of Socs3 and Regulated Expresmentioning
confidence: 99%